Measurement of the head impacts in a sub-elite Australian Rules football team with an instrumented patch: An exploratory analysis - King, D.; Hecimovich, M.; Clark, T.; Gissane, C. (International Journal of Sports Science & Coaching, 2017)
An investigation was made of the frequency, magnitude, and distribution of head impacts in Australian Football League players over a season of matches. In a prospective cohort analysis of impact magnitude, frequency, and distribution on data collected with a wireless head impact sensor worn behind the ear of 23 players, a total of 4903 impacts were recorded. Players experienced on average 407 ± 143 impacts over the duration of the study resulting in 30 ± 38 impacts per-player per-match. Linear accelerations ranged from 10 g to 153 g with a mean, median, and 95th percentile value of 17 g, 13g, and 40 g, respectively. Rotational accelerations ranged from 130 rad/s² to 21,890 rad/s² with a mean, median, and 95th percentile value of 2426 rad/s², 1556 rad/s², and 7571 rad/s², respectively. This study obtained initial measurements on the frequency, magnitude, distribution, and risk weighted exposure of head impacts in Australia Rules Football in order to better inform medical personnel in the identification and evaluation of at-risk players for concussion. The location of impacts varied considerably with the back of the head recording more total impacts than the front, side, and top. Midfielders sustained more impacts per-player, per-match, and had higher median resultant linear accelerations than forwards and defenders. The results of this study, in which most impacts were within the low severity limit for linear, rotational, HITSP, and RWECP, indicate that Australian Rules football needs to include more encompassing methods of examination of player exposure. ABSTRACT FROM AUTHOR